Attitudes and Views of University Students on Sexual Myths/Sexual Assault Myths - Doğan, Muzaffer Berna; Solmaz, Yasemin Çavuş; Eycan, Özgül; Aydın, Melek; Doğan, Merve; Güder, Pınar; Kaya, Sedanur; Bektemur, Zeynep (The Bulletin of Legal Medicine, 2022)
Objective: This research was carried out to determine the university students’ views and attitudes on sexual myths/rape myths.Methods: The sample consisted of 140 students studying at the faculty of engineering-architecture, the faculty of science and literature, and the school of health sciences. Data collection tools consist of two parts. In the first part, there are questions about sociodemographic characteristics and sexuality. In the second part, there are 15 myths about sexual myths and sexual assault myths created by researchers with the aid of literature.Results: 32,1% (n=45) of them are in the nursing department of SBYO, 25,7% (n=36) in the departments of the engineering-architecture faculty, 42,1% (n=59) in the departments of the faculty of science and literature. It was observed that the students received the most information about sexuality from communication tools (44,2%), and 48,6% (n=68) had negative thoughts about sexual intercourse before marriage. It was concluded that men, nursing and engineering-architecture faculty students and those who had a negative opinion about sexual intercourse before marriage were significantly more likely to agree with some sexual myths/sexual assault myths.Conclusion: There are those who accept these myths as true, albeit at a low rate, among university students. This may be due to gender roles, restrictive cultural norms, and the inadequacy of education and information on sexual assault and sexuality in the education system. Shaping the education system will provide university students’ awareness about sexual myths and sexual assault myths, and will help students acquire and internalize correct information.
Keywords: sexual myths; sexual assault myths; university students